1993
DOI: 10.1161/01.str.24.8.1148
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in chronic hypertension. A correlative study.

Abstract: Background and Purpose: Cerebral hypoperfusion has occasionally been reported during essential hypertension. We explored regional cerebral blood flow in a large series of neurologically asymptomatic hypertensive patients to determine relations among cerebral blood flow, concomitant main vascular risk factors, and the most common signs of end-organ damage.Methods: Regional cerebral blood flow was measured by the`33Xe inhalation method in 101 hypertensive patients without clinically apparent central nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 35 publications
6
85
1
Order By: Relevance
“…29 We also observed a similar baseline CBF in SHR and WKY animals, consistent with some human studies 1,11-14 but not others in which hypertensive subjects demonstrated a slight reduction in CBF. [8][9][10] At the same time, in other studies using the SHR and WKY models, hypertensive animals had a much higher baseline CBF value than control animals under 2% isoflurane (104 ± 23 versus 71±19 mL/100 g per minute 30 and 150±20 versus120±20 mL/ 100 g per minute. 31 ) However, the fact that we used B1% isoflurane while the other studies used 2% may account for this difference in results.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…29 We also observed a similar baseline CBF in SHR and WKY animals, consistent with some human studies 1,11-14 but not others in which hypertensive subjects demonstrated a slight reduction in CBF. [8][9][10] At the same time, in other studies using the SHR and WKY models, hypertensive animals had a much higher baseline CBF value than control animals under 2% isoflurane (104 ± 23 versus 71±19 mL/100 g per minute 30 and 150±20 versus120±20 mL/ 100 g per minute. 31 ) However, the fact that we used B1% isoflurane while the other studies used 2% may account for this difference in results.…”
Section: Discussionmentioning
confidence: 71%
“…These cerebrovascular alterations could eventually lead to a regional reduction in cerebral blood flow (CBF) and tissue oxygenation, [3][4][5] thereby increasing the risk of stroke, vascular dementia, and cognitive decline. [6][7][8] However, early-stage alterations in the cerebrovasculature are easily modified. As the cerebral regulation of blood pressure differs from the systemic regulation, treatment aimed at reducing peripheral blood pressure may not provide the necessary therapy to prevent impairments of the brain vasculature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate covariates were selected based on literature review of variables impacting CBF as well as exploratory analyses. Specifically, previous studies have identified relationships between CBF and age (Kubota et al, 1983;Naritomi et al, 1979), gender (Gur et al, 1982), and intima-media thickness (Claus et al, 1996;Nobili et al, 1993). Systolic and diastolic blood pressure, body mass index (BMI), and smoking status were also examined as potential covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Besides such systemic damage, abnormally high pressure can also threaten an optimal cerebral blood supply, as it was show in hypertensive individuals. When the CBF of hypertensive patients was measured with PET or the 133ϫe-inhalation method, and the data compared to those of normotensive individuals, reduced flow rate was recorded in the hypertensive patients [21,37,39]. In addition, the drop in CBF was less pronounced in high blood pressure patients who were receiving an anti-hypertensive treatment [39].…”
Section: Hypertension Dementia and Cbfmentioning
confidence: 99%